Pluralité des points de vue, pluralité des cultures : la construction de l’identité du moi dans les espaces insulaires - Bézert, Alexandra (Acta Universitatis Lodziensis. Folia Litteraria Romanica, 2014)
It appears that both insulars and travelling authors have interpreted the insular culture through their own depictions. These testimonies lead to cultural cross-fertilization. These diverse perspectives are an opportunity for enrichment of the islands’ cultures and a chance for them to preserve their heritage. Literacy is both a witness and a keeper of a culture. However, can the author, a sociologist, provide an objective view of the observed culture? If, in Bildungsromans, the influence of the land on the individual is obvious, the plurality of cultures is also observed within persons. This plurality of culture creates an open mindedness in each individual, which threatens the loss of his unique identity. Maintaining an insular culture may be the only way to delay its globalization.